Pengaruh Kualitas Pelayanan dan Kualitas Pembelajaran Terhadap Kepuasan Mahasiswa Dengan Metode SEM-PLS - Fransisca Debora; Hernadewita Hernadewita (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
The development of science and technology and the factors of the ASEAN economic community (MEA) which are supported by increasing industry 4.0, the government gives important responsibilities for universities to be able to produce human resources that can compete in that era. This affects universities to continue to improve in terms of the quality of learning, service quality, to provide satisfaction to students which has an influence on the productivity of higher education. In this regard, research was conducted on 120 samples of student respondents (active students, and alumni) who were used to provide information by distributing questionnaires processed by Structural Equation Modeling (SEM) - Partial Least Square (PLS). Based on the results of the analysis and discussion it can be concluded that service quality has a positive effect on student satisfaction and positively influences the productivity of higher education.